2024
DOI: 10.1111/jfb.15706
|View full text |Cite
|
Sign up to set email alerts
|

Yellowtail damselfish Chrysiptera parasema can associate predation risk with the acoustic call of a heterospecific damselfish following pairing with conspecific alarm cues

Kathryn A. Hanson,
Brooke A. Mauland,
Ananda Shastri
et al.

Abstract: The ability to detect and respond to the presence of predation risk is under intense selection, especially for small‐bodied fishes. Damselfishes (Pomacentridae) use auditory vocalizations during inter‐ and intrasexual interactions, but it is not known if they can use vocalizations in the context of predator–prey interactions. Here, we test if yellowtail damselfish, Chrysiptera parasema, can learn to associate the territorial vocalization of heterospecific humbug damselfish Dascyllus aruanus with predation risk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…While eavesdropping on heterospecific alarm calls has been observed in over 70 vertebrate species, it has been almost exclusively in mammals and birds (Magrath et al, 2015). However, in this Issue, Hanson et al (2024) buck this trend and explore interspecies call interactions in two species of damselfish using aquarium experiments.Hanson et al ( 2024) found, for the first time in a marine fish species, that yellowtail damselfish could associate predation risk from an auditory cue from another species (the humbug damselfish). The yellowtail's behavioral response to the humbug's territorial call came after the yellowtail had been conditioned with both the call and a chemical alarm cue, derived from damaged skin of another yellowtail damselfish.…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…While eavesdropping on heterospecific alarm calls has been observed in over 70 vertebrate species, it has been almost exclusively in mammals and birds (Magrath et al, 2015). However, in this Issue, Hanson et al (2024) buck this trend and explore interspecies call interactions in two species of damselfish using aquarium experiments.Hanson et al ( 2024) found, for the first time in a marine fish species, that yellowtail damselfish could associate predation risk from an auditory cue from another species (the humbug damselfish). The yellowtail's behavioral response to the humbug's territorial call came after the yellowtail had been conditioned with both the call and a chemical alarm cue, derived from damaged skin of another yellowtail damselfish.…”
mentioning
confidence: 99%
“…While eavesdropping on heterospecific alarm calls has been observed in over 70 vertebrate species, it has been almost exclusively in mammals and birds (Magrath et al, 2015). However, in this Issue, Hanson et al (2024) buck this trend and explore interspecies call interactions in two species of damselfish using aquarium experiments.…”
mentioning
confidence: 99%
See 2 more Smart Citations